United States, man and woman at general store in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Woman making purchase from clerk inside store. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3